Keefektifan Model Pembelajaran Project Based Learning (PjBL) terhadap Kreativitas Siswa pada Pelajaran SBdP Kelas V SDN 3 Mamben Lauk - Nur Oktapiani; Muhammad Tahir; Muhammad Syazali (Mataram University, 2026)
This study aims to determine the effectiveness of the Project Based Learning (PjBL) model on students' creativity in Arts, Culture, and Crafts (SBdP) learning for fifth-grade students at SDN 3 Mamben Lauk. Creativity is an important ability that needs to be developed through learning activities that encourage students to express ideas and create meaningful works. The application of innovative learning models is needed to create an active, creative, and student-centered learning process. This research used a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The research subjects consisted of two classes, namely the experimental class and the control class, each consisting of 25 students. Data collection techniques were carried out through performance tests, observations, and documentation. The research instruments were validated through expert judgment and declared feasible for use. The data analysis was conducted using normality, homogeneity, and hypothesis tests. The results showed that the data were normally distributed and homogeneous. The hypothesis test results showed a significance value of p < 0.05, indicating that H₀ was rejected and Hₐ was accepted. This means there was a significant difference between the experimental class and the control class. Therefore, it can be concluded that the Project Based Learning (PjBL) model is effective in improving students' creativity in SBdP learning for fifth-grade students at SDN 3 Mamben Lauk.